Induction of Immunotolerance in Hemophilia for High Titre Inhibitor Eradication: A Long-Term Follow-Up - Mariani, G; Solinas, S; Pasqualetti, D; Ghirardini, A; Verani, P; Buttó, S; Lopez, M; Moretti, T (Thrombosis and Haemostasis, 1989)
Three hemophiliacs with high titre inhibitor were treated with a medium-high FVIII dose schedule (100 IU/kg bw daily) with the aim of inducing the immunotolerance. These patients were followed-up extensively concerning their immunological status and HIV serology. In all of them the inhibitor disappeared and normal FVIII kinetics were obtained after 22, 15 and 29 months. After eradication of the inhibitor, no recurrence took place in any of the patients. All the patients were HIV Ab positive before the beginning of the treatment. In one of them CD4+ cells fell progessively 32 months after the treatment was started, a fullblown AIDS showed up, and the patient died 5½ years after the beginning of the treatment. In the second and third patient the CD4+ cells varied widely but remained >400/μl during the whole immunotolerance treatment. The latter two patients are AIDS and ARC free so far, but patient No. 2 developed a mild-to-severe thrombocytopenia.Considering the high cost of the treatment and the possibility that such an intensive administration of FVIII concentrates might worsen the immunological status of patients, this therapeutic procedure should only be applied with caution.
Keywords: FVIII inhibitors; High responders; HIV-infection; AIDS; Immunotolerance